Dimensiones de la Inteligencia Emocional de estudiantes regulares y con discapacidad de la Institución Educativa Juan María Céspedes del Municipio de Tuluá (2023)
The role of teachers, counselors, and psychologists is important for improving students' emotional skills and promoting a healthy and conducive learning environment. It is relevant to investigate the behavior of students in relation to their academic peers, including those with special needs for inclusive education, and analyze how emotional intelligence is managed in the inclusion and/or acceptance in a regular classroom of students with disabilities. This thesis work focuses on a specific study of analysis of the dimensions of emotional intelligence present in seventh-grade regular and disablet students of the Juan María Céspedes Educational Institution in the Municipality of Tuluá.